2011
DOI: 10.1007/s12552-011-9040-8
|View full text |Cite
|
Sign up to set email alerts
|

School-Based Racial and Gender Discrimination among African American Adolescents: Exploring Gender Variation in Frequency and Implications for Adjustment

Abstract: The present study examined school-based racial and gender discrimination experiences among African American adolescents in Grade 8 (n = 204 girls; n = 209 boys). A primary goal was exploring gender variation in frequency of both types of discrimination and associations of discrimination with academic and psychological functioning among girls and boys. Girls and boys did not vary in reported racial discrimination frequency, but boys reported more gender discrimination experiences. Multiple regression analyses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
87
4
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(108 citation statements)
references
References 52 publications
9
87
4
4
Order By: Relevance
“…During 8th and 11th grade, teacher differential treatment did not significantly predict selfconcept of math ability or math task value. This was surprising, considering previous research linking perceptions of differential treatment to decreased (domain-general) levels of student motivation, self-efficacy beliefs, and achievement (Benner and Graham 2013;Byrd and Chavous 2011;Cogburn et al 2011).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…During 8th and 11th grade, teacher differential treatment did not significantly predict selfconcept of math ability or math task value. This was surprising, considering previous research linking perceptions of differential treatment to decreased (domain-general) levels of student motivation, self-efficacy beliefs, and achievement (Benner and Graham 2013;Byrd and Chavous 2011;Cogburn et al 2011).…”
Section: Discussionmentioning
confidence: 90%
“…MADICS does not afford the capacity to calculate intraclass correlations or other informative estimates of potential bias to standard errors, due to the complexity of its data structure (i.e., participants attended 23 middle schools and 14 high schools within Prince George's County alone) and the limited number of students sampled per school. On the other hand, the failure to account for clustering may entail quite minimal bias (Heck and Thomas 2015), and a series of studies have used MADICS without adjusting for potential standard error bias (e.g., Byrd and Chavous 2011;Chavous et al 2008;Cogburn et al 2011;Gutman et al, in press;Rapa and Diemer 2016;Wong et al 2003). These limitations are offset by the affordances provided by MADICS, such as the capacity to longitudinally examine the mediated pattern of relationships between teacher differential treatment and African American students' selfconcept of math ability and math task value, which were not examined in Benner et al (2015).…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of research on discrimination in children (Cogburn et al 2011, Coker et al 2009, Pachter & Coll 2009, Sanders-Phillips 2009), indicating that exposure to discriminatory events actually begins in childhood, which has important consequences for health in childhood and adolescence (Beatty & Matthews 2009, Brody et al 2014, Matthews et al 2005, Priest et al 2013, Zeiders et al 2014), and may also be linked to adverse health in later life. As one example, a small study of pregnant African-American women found that witnessing discrimination as a child --i.e.…”
Section: Ongoing Controversies and Gaps In Knowledgementioning
confidence: 99%
“…Fisher and colleagues (2000) also found that 46% of African Americans youth reported that they were given a lower grade than they deserved because of their race or ethnicity. Research also provides evidence that African American students are more likely to be disciplined more harshly at school due to race (e.g., Chavous et al, 2008;Cogburn, Chavous & Griffin, 2011;Fisher et al, 2000;. In the same study, Fisher and colleagues (2000) found that when compared with students from other ethnic groups, African American students in particular felt that racial discrimination resulted in their wrongly being disciplined in school by teachers.…”
Section: Racial Climate and Schoolingmentioning
confidence: 99%